Positive Action in the European Union: From Kalanke to Marschall - Cox, Katherine (Columbia Journal of Gender and Law, 1998)
It is no secret that eye-catching headlines and provocative stories sell newspapers. Even so, the newspaper headlines announcing the recent Marschall decision, handed down by the European Court of Justice (“the ECJ”) in November 1997, can hardly be accused of understating the high emotion surrounding positive action. The headlines give more than a hint of some of the issues that surround this controversial topic: namely, sexism, discrimination, and equality. “COURT ALLOWS JOBS FOR THE GIRLS” announces one headline; “QUOTAS BY ANOTHER NAME” declares another. We are reminded not only of the strong feelings that positive action and quota systems in particular evoke, but also that positive action has its strong opponents and critics. In inflammatory language, one editor writes that, “German men should no more be forced to pay for the sexist sins of their fathers than for their fathers’ Nazi sins.” Evidently, gender equality is a topical issue and one that gives rise to extreme views. Other newspapers report that: “WOMEN WIN JOB RULING,” “EU COURT BACKS MOVE FOR MORE FEMALE JOBS,” and “COURT STRIKES BLOW FOR CAREER WOMEN.” The ECJ is described as having “struck a blow for women’s right to jump the job queue, shattering glass ceilings in offices across the continent.” One journalist comments wryly that positive discrimination has been declared to be a “Good Thing.” It appears that women have won (and men lost) the latest battle in the war between the sexes. Other headlines, more neutral in their coverage, inform the reader that “GERMAN GENDER-EQUALITY LAW IS UPHELD BY EUROPEAN COURT,” “COURT BACKS JOBS AFFIRMATIVE ACTION” and “COURT BACKS POSITIVE BIAS TO END GENDER IMBALANCE.” But even these “benign” headlines belie a deeper truth, which is worthy of comment. Each headline uses different terminology to express essentially one idea. The phrases “affirmative action,” “positive bias,” and “gender-equality law” are all used to refer to positive action. Yet, in practice, these terms cannot be regarded as meaning the same thing. The use of different words to convey one notion reminds us that language is powerful and not necessarily neutral. Words we use to express ideas carry connotations that go beyond the mere meaning of the words themselves. When the term “positive bias” is used, it does not come empty-handed but with negative connotations of bias and discrimination. “Affirmative action” is weighted down with the controversy and dispute surrounding it in the United States. In his article Rethinking Positive Action, McCrudden contends that groups arguing for or against a concept try to “capture” the terminology which defines it. Indeed, “affirmative action” has been “captured” to the degree that when it is used it conjures up images of discord and dispute. In 1986, when McCrudden wrote his article, he thought that the term “positive action” had appeal because it had not yet been “captured.” Over a decade later, while “positive action” may not carry quite the baggage of “affirmative action,” it has become increasingly burdened.